Effect of boosting system architecture and thermomechanical limits on diesel engine performance: Part-I—Steady-state operation. (October 2018) - Galindo, José; Climent, Hector; Varnier, Olivier; Patil, Chaitanya
Internal combustion engine developments are more focused on efficiency optimization and emission reduction for the upcoming future. To achieve these goals, technologies like downsizing and downspeeding are needed to be developed according to the requirement. These modifications on thermal engines are able to reduce fuel consumption andC O 2 emission. However, implementation of these kind of technologies asks for right and efficient charging systems. This article consists of study of different boosting systems and architectures (single- and two-stage) with combination of different charging systems like superchargers and e-boosters. A parametric study is carried out with a zero-dimensional engine model to analyze and compare the effects of these different architectures on the same base engine. The impact of thermomechanical limits, turbo sizes and other engine development option characterizations are proposed to improve fuel consumption, maximum power and performance of the downsized/downspeeded diesel engines.